Enhanching Digiital Literacy and Introduction AI Application for Learning Purposes - Soni, Mohammad; Fajriah, Yustika Nur; Nugraha, Irsyad; Nurjamin, Lucky Rahayu; Adiansyah, Adi; Isnawati, Isnawati (Fakultas Kewirausahaan Universitas Garut, 2024)
The importance of digital literacy and AI integration, aims to explore effective strategies in implementing digital literacy and introducing AI applications in the context of learning that can overcome current and future challenges. The purpose of this community service activity is to provide students with an understanding of improving digital literacy. This community service activity is carried out through lectures, collaboration, and mentoring to directly implement the use of information systems to increase learning motivation using AI applications for students of MAN 5 Garut. The results of this community service activity can be identified that through the practice of AI applications for students that can improve digital literacy.